Personal and perceived depression stigma: Magnitude and predictors in formerly depressed and never depressed individuals - Kristín Hulda Gísladóttir 1994- (2020)
Background: Stigma towards depression has been associated with a range of negative psychological and social effects. Different forms of stigma include personal depression stigma (negative attitudes towards depression in others), and perceived depression stigma (perceived attitudes of others towards depression). Magnitude of depression stigma has not been assessed in Iceland, predictors of stigma have not been clearly established, and research on differences in stigma depending on history of depression is lacking. Methods: One hundred and one individuals with a former history of depression, and fifty-six individuals with no such history, answered self-report questionnaires for depression stigma, demographic factors and clinical indicators, and depression history was assessed via interviews, as part of a larger research project. Results: Personal and perceived depression stigma was low, perceived stigma was higher than personal stigma, and higher among individuals with a history of depression than those without. Higher personal depression stigma was predicted by being male, in a relationship, lower education, perceived depression stigma, symptoms of anxiety and depression, age of onset for the first depressive episode, and less self-compassion. More perceived depression stigma was predicted by symptoms of anxiety and less self-compassion. Conclusions: Findings confirm the relationship between personal and perceived depression stigma and the relationship between various, previously studied factors, and personal depression stigma. The finding also supports that other demographic and clinical factors are associated with depression stigma. Further research should examine whether these relationships hold for more diverse groups, and why there appears to be less stigma in Iceland than in countries of previous studies. Bakgrunnur: Tengsl hafa fundist á milli fordóma gagnvart þunglyndi og neikvæðra afleiðinga, bæði sálfræðilegra og félagslegra. Þunglyndisfordómum má skipta í eigin þunglyndisfordóma (neikvætt viðhorf ...